2012
DOI: 10.2527/jas.2012-5550
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Quality Audit–2011: In-plant survey of targeted carcass characteristics related to quality, quantity, value, and marketing of fed steers and heifers1,2

Abstract: The 2011 National Beef Quality Audit (NBQA-2011) assessed the current status of quality and consistency of fed steers and heifers. Beef carcasses (n = 9,802), representing approximately 10% of each production lot in 28 beef processing facilities, were selected randomly for the survey. Carcass evaluation for the cooler assessment of this study revealed the following traits and frequencies: sex classes of steer (63.5%), heifer (36.4%), cow (0.1%), and bullock (0.03%); dark cutters (3.2%); blood splash (0.3%); ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…Dark cutting continues to occur despite preventive measures, and in the US, the proportion of dark cutting has fluctuated, decreasing from 2.3% in 2002(McKenna et al 2002) to 1.9% in 2005 (Garcia et al 2008), then increasing to 3.2% in 2012 (Moore et al 2012). The incidence of dark cutting has also increased in Canada within the last 10 yr (Jones and Tong 1989;Donkersgoed et al 1997Donkersgoed et al , 2001BCRC 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dark cutting continues to occur despite preventive measures, and in the US, the proportion of dark cutting has fluctuated, decreasing from 2.3% in 2002(McKenna et al 2002) to 1.9% in 2005 (Garcia et al 2008), then increasing to 3.2% in 2012 (Moore et al 2012). The incidence of dark cutting has also increased in Canada within the last 10 yr (Jones and Tong 1989;Donkersgoed et al 1997Donkersgoed et al , 2001BCRC 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Dark cutting continues to occur and its incidence has increased in Canada within the last 10 yr from 0.8 to 1.3% (Beef Cattle Research Council (BCRC) 2013). In Australia the incidence of dark cutting is about 10% (Meat Standards Australia (MSA) 2010), whereas in the United States of America (US) the proportion of dark cutting has increased from 1.9% in 2005 (Garcia et al 2008) to 3.2% in 2012 (Moore et al 2012). Recently, it has been indicated that improved muscling and carcass weight lowered the incidence of dark cutting (McGilchrist et al 2012), but there are contradictory reports about the effect of animal sex on the likelihood of dark cutting (Lorenzen et al 1993;Mach et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be 66 inferior in flavor and consumer acceptability [12]. The incidence of DFD in meat varies 67 markedly over different countries, often with rates of about 10%, and is the cause of 68 large economic losses [5,8,13,14]. 69 8 gels using an Ettan DALTsix vertical slab gel system (GE, Healthcare) and Tris-166 glycine-SDS (50 mM Tris, 384 mM glycine and 0.2% SDS) as electrode buffer.…”
Section: Introduction 47mentioning
confidence: 99%
“…The 2011 National Beef Quality Audit reported that 3% of carcasses sampled were graded as dark-cutters (Moore et al, 2012). Dark-cutting beef is an effect of a metabolic condition(s) due to chronic stress resulting in limited lactic acid formation in post-rigor muscles (Hendrick et al, 1959).…”
Section: Introductionmentioning
confidence: 99%